Crop Diversification in West Bengal:A District Level Analysis for the Period 1980-81 to 2011-12 - Mukherjee, Sumana; Chattopadhyay, Soumyadip (Journal of Rural Development, 2017)
This paper examines the dynamics of crop diversification in the pre and postliberalisation period addressing questions on the nature and scope of crop diversification in a small farm dominated economy like West Bengal and the factors influencing it. The analysis reflects the positive impact of operational area and cropping intensity on the degree of crop diversification. In contrast, factors like availability of irrigational facilities, degree of electrification, usage of fertilisers and price of output have a negative influence on the same in a particular region. Besides, a significant inter-district variation in the degree of crop diversification is noticed during the period under consideration. The study points out that a high level of diversification in an area does not essentially correspond to the district having a traditional resource base or a high endowment of modern inputs.